Створення нових територій природно-заповідного фонду як важливий складник розбудови структурних елементів екомережі поліської частини Сумської області - Скляр, Юрій; Скляр, Вікторія; Skliar, Iurii; Skliar, Viktoria (Східноєвропейський національний університет імені Лесі Українки, 2014)
Надано інформацію про три проектовані об’єкти природно-заповідного фонду поліської частини Сумської області. Для зазначених територій проведений аналіз стану природних комплексів та їхньої созологічної цінності. Запропоновано категорію, тип, назви та природоохоронний режим проектованих природно-заповідних об’єктів. Визначено їхню значущість та місце в розбудові екомережі Полісся Сумщини. Provided information on three projected objects of nature reserve fund Polesskaya part of Sumy region: zakazniks "Pigarevsky", "Zhuravlevy" and "Chemerichny". It is shown that natural systems areas proposed for inclusion in the reserves, are important in the formation and protection of the hydrological network of the area. Here is a vegetation typical for the Polesie part of Sumy region. Within the projected reserves are growing species of "Red Book of Ukraine» (Dactylorhiza fuchsii (Druce) Soo, Dactylorhiza incarnata (L.) Soo), as well as those that are regionally rare (Calla palustris L., Utricularia vulgaris L.). On the basis of analysis of the state of natural systems and biodiversity to the projected area of nature reserve fund proposed protection regime, as well as determined their significance and place in the econet Polissia Sumy region.
The Creation of New Areas of Nature-reserve Fund as an Important Component of the Formation of the Structural Elements of the Econet Polissya Sumy Region
Keywords: природно-заповідний фонд; екомережа; біорізноманіття; охорона екосистем; nature-reserve fund; econet; biodiversity; ecosystem protection